2021
DOI: 10.1007/s11031-021-09878-2
|View full text |Cite
|
Sign up to set email alerts
|

Compassion protects against vital exhaustion and negative emotionality

Abstract: We investigated (i) the predictive relationships of compassion with negative emotionality (a marker of susceptibility to stress) and vital exhaustion (a marker of chronic stress response) and (ii) the effect of compassion on the developmental courses of negative emotionality and vital exhaustion over a follow-up from early adulthood to middle age. We used the prospective Young Finns data (n = 1031–1495, aged 20–50). Compassion was evaluated in 1997, 2001, and 2012; and vital exhaustion and negative emotionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 81 publications
0
6
0
2
Order By: Relevance
“…An alternative explanation is that the emotion-regulation and calming aspects of trait-like compassion are some of the psychological mechanisms explaining how meditation training affects epigenetic aging ( 58 ). Compassion for others, for instance, reduces stress by increasing the ability to receive social support ( 59 ), and protects against vital exhaustion (a marker of susceptibility to stress), negative emotionality (a marker of chronic stress responses) ( 60 ), and elevated levels of cytokines (a marker of immune response) ( 12 ). Our main finding is also in line with the association observed between meditation training and telomere biology ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is that the emotion-regulation and calming aspects of trait-like compassion are some of the psychological mechanisms explaining how meditation training affects epigenetic aging ( 58 ). Compassion for others, for instance, reduces stress by increasing the ability to receive social support ( 59 ), and protects against vital exhaustion (a marker of susceptibility to stress), negative emotionality (a marker of chronic stress responses) ( 60 ), and elevated levels of cytokines (a marker of immune response) ( 12 ). Our main finding is also in line with the association observed between meditation training and telomere biology ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association from high compassion to fewer sleep difficulties may also be explained by stress regulation. Research has shown, for instance, that high compassion is associated with lower self‐reported and physiologically measured levels of stress (Abelson et al., 2014; Engert et al., 2017; Saarinen et al., 2021), including the stronger activity of the vagus nerve of the parasympathetic nervous system (Porges, 2001; Stellar & Keltner, 2017). High compassion is also found to be associated with more adaptive coping styles in stressful situations, for instance, greater acceptance in the face of adversity (Jazaieri et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…12,14 Compassion-based interventions protect nurses from negative emotionality and exhaustion. 15 Short-and long-term compassion programs impact compassion satisfaction, professional quality of life, perceived stress, and resilience. 16 Mindful self-compassion programs influence compassion satisfaction and resilience.…”
Section: Caring Science and Compassion-based Interventionsmentioning
confidence: 99%